Effects of Foeniculum vulgare ethanol extract on osteogenesis in human mecenchymal stem cells - Zahra Mahmoudi; Masoud Soleimani; Abbas saidi; Gholamreza Khamisipour; Arezoo Azizsoltani (Mashhad University of Medical Sciences, 2013)
Objective: Osteoporosis or silent disease is a major bone disorder in elderly women in current century. Estrogen has an important role in osteogenesis and prevention of bone fractures. Hormone replacement therapy (HRT) is usually accompanied by such effects as breast and ovary cancers. Thus, there is an increasing demand for replacement with plant phytoestrogens. This study is focused on determining the effects of Foeniculum vulgare extract on proliferation and osteogenesis progress in human mesenchymal stem cells. Material and Methods: Human mesenchymal stem cells were isolated and treated with different amount of plant extracts (0.5 to 100 µg/ml). Extract cytotoxicity was measured using MTT assay. The alkaline phosphatase enzyme activity was measured to evaluate the differentiation progress. Results: Results of MTT assay and alkaline phosphatase activity showed that Foeniculum vulgare extract, at range of 5 to 50 µg/ml, may positively affect cell proliferation and mineralization. The most proliferation and enzyme activity were seen with dose of 5 µg/ml. Conclusions: Foeniculum vulgare has been used in Iranian folk medicine for many years. Our in vitro study showed that Foeniculum vulgare extract has osteoprotective effects.